Perancangan Sistem Informasi Akademik Dan Pendaftaran Siswa Baru Berbasis Web Menggunakan Metode Waterfall Pada MI Jami’atul Khair Tangerang - Putri Khaerunnisa; Maulana Fansyuri (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Nowadays, information technology has experienced rapid development. The development of technology allows various kinds of activities to be carried out very quickly, precisely and accurately. MI (Madrasah Ibtidaiyah) Jami'atul Khair Tangerang is one of the leading private elementary schools in Tangerang City. The problem experienced is that the new student registration process which is carried out manually still uses handwriting in filling out the registration form and in terms of the committee itself in recording prospective new students who register. Not only that, the problem experienced by MI Jami'atul khair is that many parents complain about the absence of an academic information system application. to view student academic data online. The creation of an academic information system application and website-based registration to make it easier for students and prospective new students to register and view academic information easily using the waterfall method because this method is systematic and sequential the process also follows the flow from analysis, design, code, testing and operation. With the existence of an academic information system and online registration of new students at MI Jami'atul Khair, it makes it easier for parents and students to view academic data online, even staff are also easier to manage student data, grade data, lesson schedules, teacher data, and other data including data on students who have registered online.